(untitled) (Delito y Sociedad, 2023)
Starting from a reading of social control studies based on central notions of critical urban theory, the article proposes as a hypothesis that the production of urban space includes a para-urban dimension. To study this dimension of the phenomenon, the «urban control» category is proposed and the objective is to identify and analyze the characteristics that it assumed in the context of an urban policy aimed at the aesthetic and functional transformation of «public space» during three administrations of the Propuesta Republicana party (2007-2019) in the city of Buenos Aires. The methodology consists of the descriptive and interpretive analysis of a corpus of regulations and official documents. After reconstructing the modifications introduced by the local ruling party in the contraventional regulations and the «urban control strategies» implemented, it is concluded that during the period studied «urban control» was characterized by the combination of traditional punitive practices with other more innovative ones framed in an «hegemonic urban morality»: through schemes of legitimacy and illegitimacy, it aims to reduce the «complicity of urban exteriors» with the performance of practices classified as improper, carried out by popular classes.